Pamiętnik literacki - Towarzystwo Literackie imienia Adama Mickiewicza; Instytut Badań Literackich (Poland); Instytut Badań Literackich (Polska Akademia Nauk) (Zakład im. Ossolińskich, 1902)
"Czasopismo kwartalne poświęcone historii i krytyce literatury polskiej."
Keywords: Polish literature : History and criticism : Periodicals; 18.54 Polish language and/or literature; Polish literature; Poland